1996
DOI: 10.1074/jbc.271.46.29393
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Receptor-bound Urokinase-type Plasminogen Activator for Integrin αvβ5-directed Cell Migration

Abstract: The urokinase plasminogen activator (uPA) interacts with its cell surface receptor (uPAR), providing an inducible, localized cell surface proteolytic activity, thereby promoting cellular invasion. Evidence is provided for a novel function of cell surface-associated uPA⅐uPAR. Specifically, induction of cell surface expression of uPA⅐uPAR by growth factors or phorbol ester was necessary for vitronectin-dependent carcinoma cell migration, an event mediated by integrin ␣v␤5. Cell migration on vitronectin was block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(155 citation statements)
references
References 49 publications
5
149
0
1
Order By: Relevance
“…In addition, it has been found that uPA/uPAR complexes bind vitronectin (which in turn binds to the same av integrins as osteopontin), and that uPAR may itself physically associate with certain integrins, such that some have suggested that uPA may stimulate cell migration and invasion by non-proteolytic mechanisms as well (e.g. by modulating adhesion interactions at focal contacts, or by triggering signal transduction pathways involved in the motility response) (Andreasen et al, 1997;Yebra et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been found that uPA/uPAR complexes bind vitronectin (which in turn binds to the same av integrins as osteopontin), and that uPAR may itself physically associate with certain integrins, such that some have suggested that uPA may stimulate cell migration and invasion by non-proteolytic mechanisms as well (e.g. by modulating adhesion interactions at focal contacts, or by triggering signal transduction pathways involved in the motility response) (Andreasen et al, 1997;Yebra et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…25,60,61 The uPA receptor then focuses plasmin activation at or near the sites of focal contact between cell surface and extracellular matrix proteins. 62,63 Recent results have shown that vitronectin plays a crucial role in directing the redistribution of integrins and uPA to focal adhesion sites in several cancer cell lines, including PC cell lines. 63 Once co-localized to focal points, uPA is thought to regulate cell migration as well as pericellular proteolysis by co-ordinating focal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 In addition, uPA or plasmin is known to stimulate cell motility. 42,47,48 In vitro invasion of Matrigel, a reconstituted basement membrane, by HOXϩ1 and HOXϩ2 cells was enhanced by addition of plasminogen into the medium during the assay. Taken together, uPA and integrin ␤3 induced by HOXD3 overexpression are considered important factors involved in the marked enhancement of invasive and metastatic capacity.…”
Section: Matrix-degradative Property Of the Hoxd3 Transfectantmentioning
confidence: 99%